PENGEMBANGAN BAHAN AJAR TEMATIK ORGAN GERAK HEWAN BERBASIS NILAI-NILAI KEISLAMAN KELAS V DI MI AL-AWWAL PALEMBANG - Eni Pujiarti (Muróbbî: Jurnal Ilmu Pendidikan, 2023)
This research is an R&D (Research and Development) which aims to: 1) produce a thematic teaching material product for animal organs based on valid Islamic class V values, 2) produce a thematic teaching material for animal organs for animal organ based on class V Islamic values the practical one. The development procedure of this study adopted the ADDIE model. The stages are: 1) analysis, 2) design, 3) development, 4) implementation, 5) evaluation, but only carried out until the implementation stage (implementation). This study involved three experts, namely linguists, design experts, and material experts. Subjects one-on-one trials and small-scale trials are students of Va MI Al-Awwal Palembang class. Data collection instruments used observation, interviews, student questionnaire respondents, and validation sheets. The results of this study indicate that: 1) the thematic teaching materials of animal motion organs based on Islamic values ??of class V are declared valid with details of language validation obtaining an average score of 4.2 with very valid criteria, the results of design validation obtain an average score of 3, 4 with valid criteria and the results of material validation obtained an average score of 3.5 with valid criteria, 2.) students' responses to the thematic teaching materials of animal motion organs based on Islamic values ??of class V from the results of the one-on-one trial results obtained an average of an average score of 4.2 with very practical criteria and small-scale trials obtaining an average of 8.2 with very practical criteria.